Relationship between Sense of Coherence and oral health in adults and elderly Brazilians - Rosane Silvia DAVOGLIO; Claídes ABEGG; Victor Nascimento FONTANIVE; Mônica Maria Celestina de OLIVEIRA; Denise Rangel Ganzo de Castro AERTS; Charles Henrique CAVALHEIRO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The purpose of this study was to investigate the relationship between Sense of Coherence (SOC) and oral health clinical variables (number of teeth present and absence of need for dental prostheses). The sample consisted of 720 adults and elderly Brazilians. The data were collected at home using the SOC-13 scale - a form of clinical examination for the evaluation of oral conditions - and a questionnaire evaluating socioeconomic aspects and the use of dental services. Statistical analysis, both univariate and multivariate, was performed by Poisson regression with robust variance adjustment. The average age of the participants was 60.2 years, and they were predominantly female (57.8%). Among the participants who had a strong SOC, the absence of the need for dental prostheses was 34% higher than among those with a weak SOC, demonstrating a significant difference between the groups (PR = 1.34, 95%CI = 1.06-1.70; p = 0.015). Individuals who had a strong SOC had a 5% higher prevalence of 14 or more existing teeth than those with a weak SOC, which was statistically significant after adjustment for co-factors (PR = 1.05, 95%CI = 1.01-1.11, p = 0.033). A strong personal Sense of Coherence has a beneficial influence on the oral health of adults and older people in Brazil.